Long non-coding RNA HNF1A-AS1 regulates proliferation and migration in oesophageal adenocarcinoma cells. Issue 6 (2nd September 2013) - Yang, Xue; Song, Jee Hoon; Cheng, Yulan; Wu, Wenjing; Bhagat, Tushar; Yu, Yiting; Abraham, John M; Ibrahim, Sariat; Ravich, William; Roland, Bani Chander; Khashab, Mouen; Singh, Vikesh K; et al.
Abstract : Objectives: Long non-coding RNAs (lncRNA) have been shown to play important roles in the development and progression of cancer. However, functional lncRNAs and their downstream mechanisms are largely unknown in the molecular pathogenesis of oesophageal adenocarcinoma (EAC) and its progression. Design: lncRNAs that are abnormally upregulated in EACs were identified by RNA-sequencing analysis, followed by quantitative RT-PCR (qRTPCR) validation using tissues from 25 EAC patients. Cell biological assays in combination with small interfering RNA-mediated knockdown were performed in order to probe the functional relevance of these lncRNAs. Results: We discovered that a lncRNA, HNF1A-AS1, is markedly upregulated in human primary EACs relative to their corresponding normal oesophageal tissues (mean fold change 10.6, p<0.01). We further discovered that HNF1A-AS1 knockdown significantly inhibited cell proliferation and anchorage-independent growth, suppressed S-phase entry, and inhibited cell migration and invasion in multiple in vitro EAC models (p<0.05). A gene ontological analysis revealed that HNF1A-AS1 knockdown preferentially affected genes that are linked to assembly of chromatin and the nucleosome, a mechanism essential to cell cycle progression. The well known cancer-related lncRNA, H19, was the gene most markedly inhibited by HNF1A-AS1 knockdown. Consistent to this finding, there was a significant positive correlation between HNF1A-AS1 and H19 expression in primary EACs (p<0.01). Conclusions: We have discovered abnormal upregulation of a lncRNA, HNF1A-AS1, in human EAC. Our findings suggest that dysregulation of HNF1A-AS1 participates in oesophageal tumorigenesis, and that this participation may be mediated, at least in part, by modulation of chromatin and nucleosome assembly as well as by H19 induction.